Standard (3, 5)-threshold quantum secret sharing by maximally entangled 6-qubit states - Yinxiang Long (Nature Portfolio, 2021)
Abstract In this paper, a standard (3, 5)-threshold quantum secret sharing scheme is presented, in which any three of five participants can resume cooperatively the classical secret from the dealer, but one or two shares contain absolutely no information about the secret. Our scheme can be fulfilled by using the singular properties of maximally entangled 6-qubit states found by Borras. We analyze the scheme’s security by several ways, for example, intercept-and-resend attack, entangle-and-measure attack, and so on. Compared with the other standard threshold quantum secret sharing schemes, our scheme needs neither to use d-level multipartite entangled states, nor to produce shares by classical secret splitting techniques, so it is feasible to be realized.